Actualization of professional values in the context of formation of professionalism in future nurses - Закусилова, Тетяна Олександрівна (ScienceRise: Pedagogical Education, 2016)
Scientific views on professionalism and professional values of the specialists were elucidated. The importance of professional values in the structure of nurses’ professionalism was considered. It was noted, that the specificity of nurse’s professional activity needs the strict observance of ethical norms and rules, prohibitions and limitations that is conditioned by the professional feature – the permanent intervention in spiritual and biological life of other people. It was established, that the effective method of formation of professional values of the future specialist of nurse work is the nurse tutorship that is realized through the love to the nurse profession. The great importance in the context of formation of professional values of future nurses was gained by the spreading of foremost experience of training of students of the department “Nurse work”; discussions, competitions in the nurse mastership. The features of actualization of professional values of future nurses as a component of their professionalism were characterized. The approaches that favor actualization of professional values of the future specialists of the nurse work, especially the use of innovative pedagogical technologies, were determined